Community Structure of Gastropod in Seagrass on Intertidal Area in The Tongkeina Village of Manado City - Gladys L Saripantung; Jan FWS Tamanampo; Gaspar Manu (Jurnal Ilmiah PLATAX, 2013)
ABSTRACT Gastropod community is one of the important components of the food chain in the seagrass beds. The purpose of this study is to identify the types of gastropods and to determine population density, relative population density, species diversity, dominance and species associations of gastropod community at three study sites in Tongkeina, Manado city. The study sites were Bahowo, Batu Meja and Rap-Rap. Data were collected by sampling methods using quadratic transect technique. The study was conducted from November to December 2012. Over all, 20 species of gastropods comprising 7 families in 4 orders were collected. Among all sites, the highest density of 35,64 individuals/m2 was found in Bahowo site and the lowest density of 14,84 individuals/m2 was found in Rap-Rap site. The highest relative density was found at Batu Meja site, shown by Columbella versicolor species with relative density of 55.9%. Diversity index ranged from 1,4786 (Batu Meja) – 1,9382 (Rap-Rap). Batu Meja site shown an index value of C = 0,35 which indicating that there is dominance by 2 species, i.e.Columbella vesicolor and Columbella rusticoides, in that site.Associations between gastropod species at all three locations formed either positive or zero association, whereas negative associations between gastropod populations were not found. Keywords : community structure, gastropods, seagrass, Tongkeina, Manado  ABSTRAK Komunitas gastropoda merupakan salah satu komponen penting dalam rantai makanan di padang lamun.  Tujuan penelitian ini adalah mengidentifikasi jenis gastropoda dan mengetahui kepadatan populasi, kepadatan relative populasi, keanekaragaman spesies, dominasi dan asosiasi antar spesies gastropoda yang telah dilakukan pada tiga lokasi penelitian di kelurahan Tongkeina kota Manado. Pengambilan data dilakukan dengan metoda sampling yang menggunakan teknik transek kuadrat. Waktu penelitian pada bulan November sampai Desember 2012.  Berdasarkan hasil penelitian, diperoleh 20 spesies gastropoda yang terdiri dari 7 famili dalam 4 ordo. Kepadatan tertinggi dari semua stasiun adalah Stasiun Bahowo yakni 35,64 ind/m2, Stasiun Rap-Rap adalah stasiun yang memiliki kepadatan terendah dari ketiga stasiun penelitian yakni 14,84 ind/m2. Kepadatan relative tertinggi terdapat di Stasiun 1 (Batu Meja) yaitu pada spesies Columbella versicolor dengan kepadatan relatif  55,9 %. Indeks keanekaragaman berkisar 1,4786 (Batu Meja)–1,9382 (Rap-Rap). Stasiun Batu Meja dengan nilai indeks C=0,35 menunjukan 2 spesies yang mendominasi yakni Columbella vesicolor dan Columbella rusticoides. Asosiasi antara spesies gastropoda di ketiga lokasi membentuk asosiasi positif dan asosiasi nol, sedangkan asosiasi negative antara populasi gastropoda tidak ditemukan. Kata kunci : struktur komunitas, gastropoda, lamun, Tongkeina, Manado